KAJIAN KESESUAIAN DOLINE UNTUK BEBERAPA TANAMAN SEMUSIM DI DAERAH KARST GUNUNGSEWU DENGAN PENDEKATAN GEOMORFOLOGI (Studi kasus di kecamatan Ponjong dan Rongkop, Gunung Kidul, Yogyakata) - Joko Winarno (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2002)
The observation has a goal to obtain the answer on land problem at Ponjong and Rongkop Districts which lie on Gunungsewu area based on geomorphology approach. The case which is being observed is it low of seasonal agriculture result in that area has a relation to the land. As we know that the area (gunungsewu karst topography) has specifi cation for doline and connical hills. The observation is done by using geomorphology survey approach which emphasizes to some aspects: land form, soils, geomorphology process, interview and bibliography. Population in the observation is karst topography and karst farmers and for the sample are doline and karst farmers (land owners) that have been choosen based on purposive. And for the land sample was appointed based on geomorpho-doline character observation. In analyzing the doliize used qualitative and quantitative methods by matching between land quality and seasonal plants growth requirenments (gogo ewe, corn, peanut and soya bean). The observation result was known that : (1) doline has marginal land for the seasonal plants (gogo rice, corn, peanut and soya bean) with main limit factor is lack ofphosphor, (2) karst farmer cultivate and fertilize still traditional ways only in soils crack depth (x < 25 cm) and was done in fourth season (18th September- 12th October) so in fifth season (13th October - 8th November) gogo rice, peanut and soya bean seeds begin growing, (3) the best plant pattern is tumpangsari but in making the pattern of plant has to be tried by seeing the doline contour to the center of doline.